2021
DOI: 10.1097/md.0000000000024045
|View full text |Cite
|
Sign up to set email alerts
|

Herb-induced autoimmune-like hepatitis associated with Xiang-tian-guo (Swietenia macrophylla seeds)

Abstract: Rationale: Drug-induced liver injury (DILI) has a relatively low incidence, whereas the incidence of herb-induced liver injury (HILI) is still under investigation. As a special type of DILI, the diagnosis of drug-induced autoimmune-like hepatitis presents a persistent challenge, because this condition has partial characteristics of both DILI and autoimmune hepatitis (AIH), such as a certain history of medication use and histology that similar is to AIH. Thus, the differential diagnosis between DILI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Complementary and alternative medicine agents may also trigger autoimmune‐like hepatitis. 15 Both “classical” AIH and IMDILI require the initial administration of prednisolone followed by IST. In our patients, weaning off steroids during follow‐up was more frequent in IMDILI patients compared to those in the classical AIH group, together with a trend toward less IST to maintain biochemical remission.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Complementary and alternative medicine agents may also trigger autoimmune‐like hepatitis. 15 Both “classical” AIH and IMDILI require the initial administration of prednisolone followed by IST. In our patients, weaning off steroids during follow‐up was more frequent in IMDILI patients compared to those in the classical AIH group, together with a trend toward less IST to maintain biochemical remission.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest the inclusion of the antidepressant trazodone to the list of potentially harmful compounds. Complementary and alternative medicine agents may also trigger autoimmune‐like hepatitis 15 . Both “classical” AIH and IMDILI require the initial administration of prednisolone followed by IST.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HDS can also elicit indirect liver damage after inducing an immune-mediated response which leads to AH. A literature review identified 8 case reports of AIH induced by the Chinese herb Xiang-tian-Guo which contains Swietenia macrophylla seeds, frequently used to treat diabetes and hypertension [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic AIH triggered by the use of herbals has been documented for the Japanese multiherbal Kampo formulation Dai‐Saiko‐to ( 18 ) ; the traditional Chinese medicine, Ma huang, an ephedrine‐type alkaloid often used for weight loss resulting in fulminant exacerbation of subclinical AIH ( 19 ) ; and recently, ingestion of Xiang‐tian‐Guo (Swietenia macrophylla seeds) ingestion for 6 months resulting in HILI with AIH features on biopsy. ( 20 ) Another study showed that immunostimulatory herbal supplements containing Echinacea and algae might exacerbate pre‐existing autoimmune disease or precipitate autoimmune disease in persons genetically predisposed to such disorders. ( 21 ) HILI with AIH features, herb‐induced AIH, and flares of chronic AIH all lead to self‐limiting acute hepatitis, a severe acute liver injury requiring treatment.…”
Section: Discussionmentioning
confidence: 99%